2016
DOI: 10.1214/16-ecp17
|View full text |Cite
|
Sign up to set email alerts
|

Boundedly finite measures: separation and convergence by an algebra of functions

Abstract: We prove general results about separation and weak # -convergence of boundedly finite measures on separable metric spaces and Souslin spaces. More precisely, we consider an algebra of bounded real-valued, or more generally a * -algebra F of bounded complex-valued functions and give conditions for it to be separating or weak # -convergence determining for those boundedly finite measures that integrate all functions in F. For separation, it is sufficient if F separates points, vanishes nowhere, and either consis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Their approach rests on the Stone-Weierstrass theorem. Using Proposition 4.1 we are able to extend the results from Löhr and Rippl (2016) to the case of random measures. Proof.…”
Section: Lipschitz Functions Determine Convergence In Distributionmentioning
confidence: 84%
See 1 more Smart Citation
“…Their approach rests on the Stone-Weierstrass theorem. Using Proposition 4.1 we are able to extend the results from Löhr and Rippl (2016) to the case of random measures. Proof.…”
Section: Lipschitz Functions Determine Convergence In Distributionmentioning
confidence: 84%
“…In Kallenberg (2017), a family C ⊆ CB + b (X) satisfying condition (ii) is called an approximating class of I and it was shown that such families determine vague convergence in M(X), see (Kallenberg, 2017, Lemma 4.1). Löhr and Rippl (2016) obtained a very general result which gives sufficient conditions for a family of functions to be convergence determining for vague convergence of measures in M(X), see (Löhr and Rippl, 2016, Theorem 2.3). Their approach rests on the Stone-Weierstrass theorem.…”
Section: Lipschitz Functions Determine Convergence In Distributionmentioning
confidence: 99%
“…If, in addition, Π X is convergence determining and Y is Feller, E x [H(X t , y)] t→0 − −− → H(x, y) by (12) for all y, which implies…”
Section: Assume the Following Three Propertiesmentioning
confidence: 99%
“…For the measurability (6), we use Remark 2.4: We need to show that Π X is convergence determining and (t, x) → E y [ x AE , Y t ] is continuous. For the former, recall that by Le Cam's theorem [10] (see also [12]), the set of functions Π X ⊆ C b (E X ) on a completely regular Hausdorff space E X is convergence determining for Radon probability measures, if it is multiplicatively closed and induces the topology of E X . In our case,…”
Section: Examplesmentioning
confidence: 99%
“…We here consider the open ε-neighborhood of 0 and the closed complements (which are Polish spaces), where we want to have the restriction of our measures to converge weakly as finite measures. This is usually formalized as follows (see [DVJ08,LR16] for this object).…”
Section: Excursion Law Entrance Law and Process Conditioned On Survivalmentioning
confidence: 99%